2020
DOI: 10.3390/insects11100680
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Distribution and Burst of Nuclear Mitochondrial DNA Sequences (NUMTs) in Fig Wasp Genomes

Abstract: Mitochondrial DNA sequences can be transferred into the nuclear genome, giving rise to nuclear mitochondrial DNA sequences (NUMTs). NUMTs have been described in numerous eukaryotes. However, the studies on the distribution of NUMTs and its influencing factors are still inadequate and even controversial. Previous studies have suggested that Hymenoptera may be a group rich in NUMTs, in which we selected 11 species of fig wasps (Chalcidoidea, Hymenoptera) to analyze the distribution and evolution of NUMTs at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Our results suggested that, in all of the 17 species, the AT contents of NUMT flanking sequences as a whole, upstream flanking sequences, and downstream flanking sequences are all higher than those of the whole nuclear genome (Figure 5), indicating a preference of the AT-rich sequence for NUMT insertion in the bumblebee nuclear genome. The preference of NUMTs for AT-rich regions has also been reported in fig wasp genomes [34]. Notably, the AT content of the NUMT upstream flanking sequence is consistently higher than that of the downstream flanking sequence in all of the 17 species (Figure 5).…”
Section: Molecular Features Of Numts In Bumblebee Nuclear Genomessupporting
confidence: 71%
“…Our results suggested that, in all of the 17 species, the AT contents of NUMT flanking sequences as a whole, upstream flanking sequences, and downstream flanking sequences are all higher than those of the whole nuclear genome (Figure 5), indicating a preference of the AT-rich sequence for NUMT insertion in the bumblebee nuclear genome. The preference of NUMTs for AT-rich regions has also been reported in fig wasp genomes [34]. Notably, the AT content of the NUMT upstream flanking sequence is consistently higher than that of the downstream flanking sequence in all of the 17 species (Figure 5).…”
Section: Molecular Features Of Numts In Bumblebee Nuclear Genomessupporting
confidence: 71%
“…To identify numts within a genome that are the result of post insertion duplications rather than mitochondrial insertions a duplicated flanking region analysis was preformed (Liang et al, 2018;Wang et al, 2020). All-against-all BLAST search of numts longer than 300 bp within a genome with a flanking region of 200 bp from each side was performed.…”
Section: Identification Of Duplicated Numtsmentioning
confidence: 99%
“…Numts were shown to be enriched in the regions of transposable elements (Mishmar et al, 2004;Tsuji et al, 2012;Michalovova et al, 2013;Hazkani-Covo and Martin, 2017). Moreover, transposable elements were shown to be a driving force for bursts of post-insertion numt duplication (Wang et al, 2020). To determine whether the observed enrichment of numt accumulation was the result of increased insertions from the mitochondria or of numt duplications within the nucleus, numts followed by similar flanking regions of at least 50 bp were identified.…”
Section: Nuclear Pseudogenes Of Mitochondrial Origin Insertion Rate I...mentioning
confidence: 99%
“…The incidence of NUMTs is influenced by diverse factors. Some are associated with genome size (e.g., frequency of double-stranded breaks, duplication via repetitive elements), but others are not (e.g., mitochondrial damage, cellular stress) so the linkage between the incidence of NUMTs and genome size is unpredictable (Antunes & Ramos, 2005;Hazkani-Covo et al, 2010;Ricchetti et al, 2004;Richly & Leister, 2004;Gerstein and Zheng, 2006;Wang et al, 2020). We detected a significant positive correlation between genome size and NUMT count, but the low coefficient of determination (ρ = 0.33) helps to explain the variable associations noted in earlier studies.…”
Section: Patterns Of Numt Abundance Among Speciesmentioning
confidence: 99%
“…The resultant pseudogenes, termed NUMTs, are prevalent throughout the animal kingdom (Bensasson, Zhang, Hartl, & Hewitt, 2001;Hazkani-Covo, Zeller, & Martin, 2010;Richly & Leister, 2004), but the factors responsible for their considerable variation in abundance among species is uncertain (Bensasson et al, 2001;Hazkani-Covo et al, 2010;Richly & Leister, 2004;Song, Buhay, Whiting, & Crandall, 2008). Some studies have reported a correlation between genome size and NUMT counts (Bensasson et al, 2001;Hazkani-Covo et al, 2010), but others have not (Gerstein & Zheng, 2006;Richly & Leister, 2004;Wang, Liu, Miao, Huang, & Xiao, 2020). NUMT frequency has also been linked to environmental factors (Gerstein & Zheng, 2006;Ricchetti, Tekaia, & Dujon, 2004;Song, Jiang, Yuan, Guo, & Miao, 2013), cellular stress (Bensasson et al, 2001;Hazkani-Covo et al, 2010), and population dynamics (Antunes & Ramos, 2005;Deceliere, Charles, & Biémont, 2005) The evolutionary implications of NUMTs have attracted considerable attention (Balakirev & Ayala, 2003).…”
Section: Introductionmentioning
confidence: 99%